Interactions of Lifestyle Factors on the Risk of Anemia Among Taiwanese Adults. (7th June 2021) - Paramastri, Rathi; Hsu, Chien-Yeh; Lee, Hsiu-An; Chao, Jane
Abstract: Objectives: The aim of this study was to investigate the association of lifestyle factors with the risk of anemia among adults in Taiwan. Methods: This cross sectional study included 118, 924 (43, 055 men and 75, 869 women) participants aged 20–45 years, who had health examination including blood tests, anthropometric measurements, and questionnaires to collect demographic, lifestyle, and dietary data at Mei Jau (MJ) Health Screening Center between 2000 to 2015. We evaluated the interactive associations of smoking, alcohol drinking, sleeping habit, physical activity, and dietary habit on the risk of anemia among study participants. The multivariable regression analysis was performed to examine the interactive correlations of lifestyle factors on the risk of anemia. Relative excess risk due to interaction (RERI) and attributable proportion (AP) were used for the estimation of additive interactions. The dietary pattern was derived by reduced rank regression. Results: The anemia-inflammatory dietary pattern was heavily loaded on eggs, meat, organ meats, rice and flour products, fried rice or flour, sugary beverages, fried foods, and processed foods. Participants who actively smoked and had less sleep duration (< 6 hours/day) significantly increased the risk of anemia (OR = 1.03, 95% CI: 1.01, 1.30, RERI = 0.13, 95% CI: 0.01, 0.24, AP = 0.31, 95% CI: 0.19, 0.35, all P interaction  < 0.05) compared to those who were non-smokers and had longer sleep duration (³ 7 hours/day). In addition, the interaction of less physically active (≤2 hours/week) and high adherence to anemia-inflammatory dietary pattern was positively correlate with the risk of anemia (OR = 1.10, 95% CI: 1.03, 1.18, RERI = 0.18, 95% CI: 0.02, 0.34, AP = 0.15, 95% CI: 0.08, 0.23, all P interaction  < 0.05). Conclusions: Smoking, less sleep duration (<6 hours/day), less physical activity (≤2 hours/week), and high adherence to anemia-inflammatory dietary pattern are associated with an increased risk of anemia. Funding Sources: This study had no funding source.